2014
DOI: 10.1155/2014/519615
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties of a Standardized Extract fromMyracrodruon urundeuvaFr. All. (Aroeira-Do-Sertão), as Evaluated by a Parkinson’s Disease Model in Rats

Abstract: Myracrodruon urundeuva Fr. All. (Anacardiaceae) is a Brazilian medicinal species, which is common to the Northeastern Brazilian semiarid region, whose stem-bark is widely used in folk medicine. It is an endangered species, presenting as main bioactive components tannins and chalcones. In this work, we studied the neuroprotective effects of a standardized extract from cultivated M. urundeuva (SEMU), in a model of Parkinson's disease. Thus, a unilateral injection of 6-OHDA was done into the rat right stratum. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 44 publications
3
25
0
3
Order By: Relevance
“…The average height of the shoot sampled was 40-50 cm (Calou et al, 2014;Bandeira, 2002). Before drying, the stems was manually separated from the leaves.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The average height of the shoot sampled was 40-50 cm (Calou et al, 2014;Bandeira, 2002). Before drying, the stems was manually separated from the leaves.…”
Section: Plant Materialsmentioning
confidence: 99%
“…They have been extensively investigated in the medical sciences because of their great potential for health promotion as well as for the prevention of natural diseases. In addition, reports have shown that these herbal products and bioactive compounds are able to reduce the oxidative damage induced by free radicals and oxygen reactive species under oxidative stress (Gupta and Sharma, , Calou et al , , Izzo et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown promising neuroprotective properties attributed to plants such as Amburana Cearenses (Amburoside A) (Calou et al , ), Camellia sinenses (catechins and polyphenols) (Guo et al , ), Gynostemma pentaphyllum (saponin extract) (Choi et al , 2010), Pueraria lobata (Puerarin) (Zhu et al , ), Alpinia oxyphylla (protocatechuic acid) (Zhang et al , ), Cistanches salsa (glycosides or phenylethanoid) (Chen et al , ; Zhao and Pux, ), Spirulina platensis (olysacharide) (Zhang et al , ), and Astragalosídeo membranáceus (saponin triterpenoid tetracílcioco) (Chan et al , ). In fact, the latter was able to reduce the loss of dopaminergic neurons in a PD model induced by 6‐OHDA, where the treated group showed intact germination, an increased number of neurites and higher levels of TH and nitric oxide synthase‐immunoreactive nerves (Chan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown plants with neuroprotective properties capable of protecting from PD damage. These include plants such as Amburana Cearenses (Amburoside A) [5], Myracrodruon urundeuva (tannins and chalcones) [45], Camellia sinensis (catechins and polyphenols) [46], Gynostemma pentaphyllum (saponin extract) [47], Pueraria lobata (Puerarin) [48], Alpinia oxyphylla (protocatecholic citric acid) [49], parsley Cistanches salsa (phenylethane glycosides) [50,51], Spirulina platensis (polysaccharide) [22] and Astragalus membranaceus (triterpenoid saponin), as mentioned in a review study [9,39].…”
Section: Parkinson's Diseasementioning
confidence: 99%